Inside Cover: Core–Shell Crystals of Porous Organic Cages (Angew. Chem. Int. Ed. 35/2018). Issue 35 (21st June 2018) - Jiang, Shan; Du, Yi; Marcello, Marco; Corcoran, Edward W.; Calabro, David C.; Chong, Samantha Y.; Chen, Linjiang; Clowes, Rob; Hasell, Tom; Cooper, Andrew I.
Abstract : Core–shell crystals of porous materials allow multiple functionalities to be used synergistically, for example, by choosing the core material for capacity and the shell for selectivity or surface properties. The few previous examples have all been based on frameworks, but in the Communication onpage 11228, T. Hasell, A. I. Cooper et al. present the first report of core–shell crystals formed from porous molecules, in this case porous organic cages, which are directed by chiral recognition. Depicted are octahedral crystals with a fluorescent cage as the core, and a non‐fluorescent cage shell layer growing on the surface.